The contribution of synaptic location to inhibitory gain control in pyramidal cells. Issue 5 (23rd September 2013) - Pouille, Frederic; Watkinson, Oliver; Scanziani, Massimo; Trevelyan, Andrew J.
Abstract: The activity of pyramidal cells is controlled by two opposing forces: synaptic inhibition and synaptic excitation. Interestingly, these synaptic inputs are not distributed evenly across the dendritic trees of cortical pyramidal cells. Excitatory synapses are densely packed along only the more peripheral dendrites, but are absent from the proximal stems and the soma. In contrast, inhibitory synapses are located throughout the dendritic tree, the soma, and the axon initial segment. Thus both excitatory and inhibitory inputs exist on the peripheral dendritic tree, while the proximal segments only receive inhibition. The functional consequences of this uneven organization remain unclear. We used both optogenetics and dynamic patch clamp techniques to simulate excitatory synaptic conductances in pyramidal cells, and then assessed how their firing output is modulated by gamma‐amino‐butyric acid type A (GABAA ) receptor activation at different regions of the somatodendritic axis. We report here that activation of GABAA receptor on the same dendritic compartment as excitatory inputs causes a rightwards shift in the function relating firing rate to excitatory conductance (the input–output function). In contrast, GABAA receptor activation proximal to the soma causes both a rightwards shift and also a reduction in the maximal firing rate. The experimental data are well reproduced in a simple, four compartmental model of a neuron with inhibition either on the same compartment, or proximal, to the excitatory drive. Abstract : e00067 Abstract : Cortical pyramidal cells receive excitatory and inhibitory synaptic drives but these are not distributed equivalently across the dendritic tree. The distal tree receives both excitation and inhibition, and the effect of inhibition there is a subtractive gain change. In contrast the proximal inhibition produces a marked divisive inhibitory effect.